2013
DOI: 10.1186/1546-0096-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength, physical fitness and well-being in children and adolescents with juvenile idiopathic arthritis and the effect of an exercise programme: a randomized controlled trial

Abstract: BackgroundDecreased muscle strength, fitness and well-being are common in children and adolescents with juvenile idiopathic arthritis (JIA) compared to healthy peers. Biological drugs have improved health in children with JIA, but despite this pain is still a major symptom and bone health is reported as decreased in the group. The improvement made by the biological drugs makes it possible to more demanding exercises. To jump is an exercise that can improve bone heath, fitness and muscle strength. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 36 publications
1
61
0
8
Order By: Relevance
“…The CHQ-PF50 is a 50-item, parent-completed questionnaire designed to measure the physical and psychosocial well-being of children between the ages of 5 and 18. The CHQ-PF50 has established reliability and validity and has been widely used in studies of chronic illness in childhood [29-31]. Items are measured on a Likert scale, summed for each subscale and linearly transformed to a 0 to 100 scale, where higher scores reflect better functioning.…”
Section: Methodsmentioning
confidence: 99%
“…The CHQ-PF50 is a 50-item, parent-completed questionnaire designed to measure the physical and psychosocial well-being of children between the ages of 5 and 18. The CHQ-PF50 has established reliability and validity and has been widely used in studies of chronic illness in childhood [29-31]. Items are measured on a Likert scale, summed for each subscale and linearly transformed to a 0 to 100 scale, where higher scores reflect better functioning.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on physical exercise programs in JIA patients show that exercise training is beneficial for this population [5,15,21,[27][28][29][30][31][32][33][34][35][36]. The trends for outcome measures all point to benefits of exercise, with increased strength and range of motion, improved joint stiffness, and better quality of life [37].…”
Section: Clinical Effects Of Exercise In Jia Patientsmentioning
confidence: 95%
“…The chronic inflammatory systemic feature of JIA is mediated by cytokine products of an activated immune system, including tumor necrosis factor (TNF)-α, interleukin-1 (IL-1) and interleukin-6 (IL-6) [3,4]. Aftereffects of JIA can include pain, fatigue, reduced fitness, reduced activity, sleep disturbances, muscle atrophy, decreased bone mineral composition (BMC) and impaired quality of life [1,5], as well as growth retardation (with low IGF-1 levels in all disease onset subtypes) [6]. Furthermore, chronic inflammation can lead to numerous abnormalities including anorexia, cachexia, cachectic obesity, dyslipidemia and insulin resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Functional ability in patients with juvenile idiopathic arthritis (JIA) and their prognosis have improved considerably over the last decade due to early, targeted treatment with biologics such as etanercept . Consequently, a motivating approach to physical activity and participation in sport has emerged, because studies have shown that physical activity and exercise training in patients with JIA are both safe and beneficial in terms of numerous health and disease outcomes (e.g., quality of life, cardiovascular fitness, muscle strength, pain, number of swollen joints) . Nevertheless, children with JIA are still less physically active , participate less often in competitive sports, and spend more time sedentary compared with their peers without JIA .…”
Section: Introductionmentioning
confidence: 99%